FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN HEALTH LITERACY PADA MAHASISWA KEPERAWATAN DI UNIVERSITAS UDAYANA DENPASAR, BALI - Made Dwi Mohini; Ni Komang Ari Sawitri; I Gusti Ayu Pramitaresthi (Coping: Community of Publishing in Nursing, 2021)
Health literacy is one of health determinants. Low use of healthcare, preventine services, and less participation of health promoting behaviours are associated with low level of health literacy. Health literacy levels of nursing students are important because nursing student is a future healthcare profesional who has vital role as an educator. The aimed of this study is to asses the related factors of health literacy of nursing student in Udayana University. The study types is descriptive correlative with cross-sectional approach. Proportionate Stratified Random Sampling was applied and this study conducted with 148 participants from four different grades. This study used Participants Characteristic Form and Short-Form Health Literacy Survey Tool (HLS-SF-12) as data collection tool. Descriptive statistics, Central Tendency, Gamma correlation analysis, and Contingency Coefficent correlation analysis were used for data analysis. The result of statistic test showed that no significant correlation between grades, gender, parents highest educational level, presence of health problem, and frequency of internet use for health purposes with health literacy (p=0,232) of nursing student in Udayana University. Nursing students in Udayana University have a low level of health literacy. Health literacy levels of nursing student play an important role for their health and role as health professional in the future. Based on this study result, it is suggest for nursing lecturer to intergrated and addressed health literacy into student learning process like include health literacy in health promotion subject.